(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose – The training and development is growing as an essential component of creating an approach of green workforce able to improve green practices as firms consider sustainability and environmental responsibility increasing. The aim of the study to provide a broad overview of the connection between green training and development programs and how they impacts on job performance. Design/Methodology/Approach – This study was carried out using the advanced framework of green practices .The questionnaire was prepared and distributed among 350 employees working in an IT Sector .The population was selected using stratified random sampling.